Women Empowerment for Poverty Reduction in Ring-1 Rural Area of a Cement Company in Tuban, East Java Province, Indonesia - Rustinsyah Rustinsyah (Masyarakat, Kebudayaan dan Politik, 2018)
The existence of a cement company in a rural area may influence the local people, including women who are not employed by the company. This study aims at presenting the case of women empowerment in a Ring-1 area of a cement company in Indonesia. The research used qualitative approach. The results show that the company’s existence with its CSR programs have helped empowering rural women in social, educational, religious, organizational, and economic aspects. The social aspect is shown in the health programs. The educational aspect can be seen in the provision of scholarships for formal education and non-formal training. The religious aspect is actualized in the form of incentives for religion teachers and religious festivals. The organizational aspect is shown in the involvement of women in PKM management. Finally, the economic aspect includes: a) the construction of village road infrastructure as compensation of taxes derived from the company; b) the inclusion of workers from outside the village encourages the emergence of food stalls, grocery stalls, gasoline kiosks, and boarding houses; and c) the development of traditional markets. This study confirms that the company’s existence has encouraged rural women to improve their livelihoods and help alleviate their families from poverty.